The Impact of Preventive Protocols on Oral Health Outcomes in Cancer Patients Undergoing Chemotherapy or Radiotherapy: A Systematic Review and Meta-Analysis - Carol Moussa; Laurent Estrade; Jeremy Glomet; Gael Y. Rochefort; Frédéric Denis; Maha H. Daou (Diseases, 2025)
Background/Objectives: Cancer patients undergoing chemotherapy (CT) or radiotherapy (RT) are at increased risk of oral complications. Preventive dental care has been proposed to mitigate these risks, yet its effectiveness is not sufficiently evaluated. This systematic review and meta-analysis aimed to assess the impact of preventive oral health interventions on key clinical outcomes in oncology patients. Methods: A systematic search of MEDLINE, Embase, and CENTRAL databases was conducted (March 2025), adhering to PRISMA guidelines with a PROSPERO-registered protocol (CRD 420251006799). Eligible studies included randomized trials, cohort studies, and pre–post intervention studies evaluating preventive dental care in patients receiving CT or RT. The outcomes included gingival index (GI), dental caries (DMFT), plaque levels, and periodontal health. Meta-analyses were performed on GI and DMFT outcomes using random-effects models. Results: Eleven studies were included in the qualitative synthesis and four in the meta-analyses. Preventive interventions, such as fluoride applications, oral hygiene education, and regular professional cleanings, were associated with stabilization or improvement of gingival health. The pooled estimate for GI showed no significant deterioration over time (MD = −0.05, 95% CI: −0.34 to 0.24, p = 0.72). For DMFT, a slight but significant increase was observed (MD = 1.07, 95% CI: 0.08 to 2.05, p = 0.03), suggesting a continued risk of caries despite intervention. Conclusions: Preventive dental care interventions appear to support the maintenance of gingival health in cancer patients undergoing CT or RT. However, despite these interventions, a slight increase in dental caries was still observed, indicating that preventive strategies may not fully eliminate the risk of caries. These findings highlight the importance of sustained and individualized oral health programs as part of comprehensive oncology care. Future studies using standardized protocols and longer follow-up periods are needed to better evaluate their long-term effectiveness across diverse cancer populations.